A 3D CFD analysis of flow past a hipped roof with comparison to industrial building standards - Khalil, Khalid; Khan, Huzafa; Chahar, Divyansh; Townsend, Jamie F.; Rana, Zeeshan A. (Techno Press, 2022)
Three-dimensional (3D) computational fluid dynamics (CFD) analysis of flow around a hipped-roof building representative of UK inland conditions are conducted. Unsteady simulations are performed using three variations of the k-ϵ RANS turbulence model namely, the Standard, Realizable, and RNG models, and their predictive capability is measured against current European building standards. External pressure coefficients and wind loading are found through the BS 6399-2:1997 standard (obsolete) and the current European standards (BS EN 1991-1-4:2005 and A1:20101). The current European standard provides a more conservative wind loading estimate compared to its predecessor and the k-ϵ RNG model falls within 15% of the value predicted by the current standard. Surface shear stream-traces and Q-criterion were used to analyze the flow physics for each model. The RNG model predicts immediate flow separation leading to the creation of vortical structures on the hipped-roof along with a larger separation region. It is observed that the Realizable model predicts the side vortex to be a result of both the horseshoe vortex and the flow deflected off it. These model-specific aerodynamic features present the most disparity between building standards at leeward roof locations. Finally, pedestrian comfort and safety criteria are studied where the k-ϵ Standard model predicts the most ideal pedestrian conditions and the Realizable model yields the most conservative levels.
Keywords: CFD (Computational Fluid Dynamics); design codes and standards; pedestrian wind comfort; steady/ unsteady aerodynamic force; turbulence; wind loads